Chemical genetic analysis of FTY720‐ and Ca2+‐sensitive mutants reveals a functional connection between FTY720 and membrane trafficking. (27th August 2020) - Hagihara, Kanako; Kanda, Yuki; Ishida, Kouki; Satoh, Ryosuke; Takasaki, Teruaki; Maeda, Takuya; Sugiura, Reiko
Abstract: FTY720, a sphingosine‐1‐phosphate (S1P) analog, is used as an immune modulator to treat multiple sclerosis. Accumulating evidence has suggested the mode of action of FTY720 independent of an S1P modulator. In fission yeast, FTY720 induces an increase in intracellular Ca 2+ and ROS levels. We have previously identified 49 genes of which deletion causes FTY720 sensitivity. Here, we characterized the FTY720‐sensitive mutants in terms of their relevance to the Ca 2+ homeostasis and identified the 16 F TY720‐ and C a 2+ ‐s ensitive mutants ( fcs mutants). Most of the FTY720‐sensitive mutants showed elevated Ca 2+ levels and exhibited Ca 2+ dysregulation by FTY720 treatment. One of the functional categories among the genes whose deletion renders cells susceptible to FTY720 and Ca 2+ include the Golgi/endosomal membrane trafficking. Notably, FTY720, but not phosphorylated FTY720 incapable of inducing Ca 2+ increase, inhibited the secretion of acid phosphatase in the wild‐type cells. Importantly, secretory defects of the Golgi/endosomal trafficking mutants, Vps45, or Ryh1 deletion, were further exacerbated by FTY720. Our fcs mutant screen also identified the adenylyl cyclase‐associated protein Cap1 and a Rictor homolog Ste20, whose deletion markedly exacerbated FTY720‐sensitive secretory impairment. Collectively, our data may suggest a synergistic impact of FTY720 combined with secretion perturbation on proliferation and Ca 2+ homeostasis. Abstract : FTY720 is approved as an immune modulator for the treatment of multiple sclerosis. Here, we characterized the FTY720‐sensitive mutants and have presented chemical‐genetic evidence that FTY720 functionally links to the membrane trafficking pathway, especially at the step of the secretion process.